The frequency and seasonal variations in juvenile outpatients treated in a dermatology polyclinic - Cicek, Demet; Kandi, Basak; Oguz, Sevilay; Ucak, Haydar; Saral, Yunus; Kurt, Abdullah (Wiley-Blackwell, 2008)
Objective This study was carried out to evaluate the frequency and seasonal characteristics of dermatological problems of juvenile outpatients in the dermatology polyclinic. Material and method Children under the age of 17 treated in an outpatient setting in our polyclinic within a 10-year period were retrospectively evaluated. Results The study registered a total of 3244 patients, of whom 1651 (50.90%) were females, and 1593 (49.10%) were males. The largest group was infectious diseases, with 1031 patients (31.78%). This was followed by the dermatitis group with 635 patients (19.57%). The months when the number of presentations at the hospital was the highest were August and November, and the months with the lowest number of presentations were January and July. Conclusion In the present study we found that the most frequent cause of hospital visits of juvenile outpatients at our polyclinic was infectious diseases and dermatitis, and that there was significant correlation between diseases and seasons.
Keywords: Pediatric Dermatology; Childhood; Diseases